Do Public School Choice Policies Segregate Schools? Dynamic Effects in Michigan - Danielle Sanderson Edwards; Kaitlin P. Anderson (AERA Open)
Interdistrict choice has the potential to exacerbate or alleviate between-district segregation—an increasingly pervasive form of U.S. school segregation—by allowing students to attend schools in districts where they do not reside. Prior research concentrates on the effects of charter schooling on segregation within districts and counties. We used longitudinal enrollment and demographic data from Michigan to examine the impacts of both interdistrict and charter school choice on racial and economic segregation within and between districts in a single setting. We estimated these effects by leveraging between-grade differences in choice use within school systems and years. We confirmed findings from previous research that increases in charter school enrollment increase within-district racial and economic segregation. We also found that the effects of interdistrict choice on both within- and between-district segregation vary with the presence of charter schools.